IMPLEMENTASI KEBIJAKAN PENCEGAHAN dAN PENANGGULANGAN HUMAN IMMUNODEFICIENCY/AQUIRED IMMUNE DEFICIENCY SYNDROME (HIV/AIdS) dI KOTA SURAKARTA - Siti Wahyuningsih; Widodo.T Novianto; Hari Purwadi (HUKUM PEMBANGUNAN EKONOMI, 2017)
AbstractThis Articel to analyze the implementation of policy on the prevention and combat of Human Immunodefisiency Virus and Aquired Immune Deficiency Syndrome (HIV/AIDS) in Surakarta City. This type of research in writing this is a non-doctrinal/empirical, with basing on the concept of the law of the 5th. The form used is the research diagnostic analysis. The data type of the data source, and the primair include primary and secondary legal materials. Data analysis using qualitative analysis. Based on the results of research and discussion with respect to issues that are examined, it can be summed up as follows : (1) Factors that become the cause of inadequate response to the HIV and AIDS amongst others caused the problem of HIV and AIDS has not been considered a priority issue by the health sector as well as the development of related sectors; (2) the political support that has not been adequately against the program; (3) yet uncoordinated Commission Response AIDS (KPA) and the SKPD of Surakarta City either the direction of development, planning and implementation of policies and programs regarding the Decree despite various efforts for tackling even the financing has been issued; and (4) the still inadequate dissemination of information and access to health services and the availability of VCT services, ARV existence for sufferers and those at high risk with HIV/AIDS. The steps that must be performed in order to cope with HIV/AIDS in Surakarta, among others : (1) Aspects of the substance of the law with further strengthen runway operations mainly technical instructions and guidelines that govern the start of planning, implementation, evaluation, monitoring, sanctions; (2) Aspects of structure/function and by improving the institutional tasks of KPA either in quality, as well as institutional manegement KPA. (3) Aspects of culture either by increasing the involvement of the population of Key Non Governmental Organizations (NGOs) care about HIV/AIDS and high risk groups in planning the program and run the program as well as an evaluation of the program as a Field Officer (FO), Counselor, Case Manager. The establishment of culture/culture done by influencing the attitudes and behavior of continuously/routine so that you can understand, addressing the process of countermeasure and empathy, so as to minimize the discrimination against People Living with HIV/AIDS (ODHA). Keywords: Implementation – Policy – HIV/AIDS – Surakarta